Proposed new design for Petronas Adventure Team Corporate Centre at No.7,Jalan Kia Peng, Kuala Lumpur / Diyana Mohd Amin - Mohd Amin, Diyana (Faculty of Architecture, Planning and Surveying, 2008)
This thesis is basically to explain entirely about a proposed new design for Petronas Adventure Team (PAT) Corporate Centre. It has been divided into several chapters according to stages and categories. In the 1st chapter readers will be introduced to the project, which includes project’s mission and objectives, scope of work and thesis methodology. The project’s objective is mainly for the organization to have its own coroorate center which to have their character and style translated into the spaces. As for the sequence of project brief, the 2 chapter contains information and data about the client which is Petronas Adventure Team. In this chapter readers will get to know solely on client’s background, activities, mission and vision and the organization’s system. PAT is an organization that has its own management board and their main activity every year is an expedition to selected countries with the average range of 2 months expedition time. The system, the needs and the activities have been created specifically for the team. Thus, every detail of the client’s background is always some important information to be notified by the designer. Furthermore in chapter 3 there are facts and information gathered and stated regarding the site proposed for the project. In this chapter, detail explanations have been provided on the aspects of evaluation while selecting new site for a particular project. Also, there are images and diagrams to support all the statements and for the readers to understand better on each topic mentioned. As readers go along there is a chapter regarding case study, the functions and the usage of corporate centre and the space requirements, all in chapter 4. The function of having a case study is for the designer to capture better understanding on space requirements for the specific type of project. In chapter 5 the readers will be explained on the client’s needs and requirements and also the scope of work for the designer to do the project. Later in chapter 6, the project will move on to the next stage which is the design stage. Chapter 6 will basically starts with conceptual development, style, images and design objectives that are base on the study and analysis from all 5 chapters before. Concept is something that will brings out the space character and will reflect client’s image. “Urban Adventure” with the touch of “dynamic urban” reflects PAT the best for the team is already a symbol of strength, intelligent outdoor, and with the image of a big name, Petronas. Chapter 6 also presents the development of design, including all the preliminary design materials. As for conclusion, this project has been proceed after some observations and evaluations on issues, with the compatibility of the budget and funding stability, and after more research and surveys had been done in order to make sure that this project will achieve the target and standard the client desires.